Ideologi dan Politik dalam Proses Awal Kodifikasi Hadis - Zamzami, Mohammad Subhan (Religió: Jurnal Studi Agama-agama, 2013)
The problem of Hadits is more complex than al-Qur’ân in the perspective of Islamic theological sect. Al-Qur’ân had been codified in the early Islamic era which is in the period of Abu Bakar as Siddîq, initiated by Umar Bin Khat}t}âb under the command of Zayd Bin Thâbit. Meanwhile, the writing text and hadith codification in Khawârij, Shî’ah and Sunni tradition is still leaving the contradicted theological-political claims. This claim constitutes a common phenomenon that often happened and found in comparative study of religious sect. it is because every religious sect wants to legalize their religious ritual validity by finding a base of religious primer resources which is al-Qur’ân as the first Islamic holy text and hadith as the second one. This article highlights the politics and ideology in the early hadith codification period. It attempts to see the conflict interest of the Sunnite, Shî’ites, and Khârijities groups in which they were composing prophet traditions based on their doctrine and ideological biases. Based on their authoritative hadith books, hadith sciences, and historical literatures with regard to the historical-comparative methodology, this article suggests that they have different traditions of hadith codification which are influenced by ideological and political rivalry among them; and they also produce different hadith, authoritative hadith books, and religious traditions.